STUDENTS’ RESPONSES TOWARDS SELF-SELECTED READING IN EXTENSIVE READING CLASS - Novandy Adhitya; Jeneng Novita (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
Extensive Reading is a method in which the participant engages in the activity by reading more books from a greater variety of genres outside of the classroom to read for pleasure. As a result, pupils may choose the reading content that they are interested in reading. The following were the goals of the research named Students' Responses to Self-Selected Reading in Extensive Reading class, which was conducted: 1) To determine the kinds of reading students choose in Extensive Reading class, and 2) To observe the student's reactions to self-selected Reading in Extensive Reading class, the following research was conducted: By the academic year 2020/2021, the students of the English Education Department at one of Cimahi's colleges were in their third semester, which served as the primary topic of this research. It was decided to utilize a descriptive qualitative approach for this investigation. Document analysis, as well as interviews, were used in the data collection process. The results revealed that students choose various readings for Extensive Reading, including short stories, novels, articles, news, books, biographies, song lyrics, and other kinds of material. Regarding the study second research question, the student's answers to self-selecting for Extensive Reading were consistent, with the following replies: it was easier; the students were happier, and there was no burden in deciding to do it. According to the research findings, the students chose more kinds, and they were pleasant to work with and seemed to enjoy themselves.